Pemikiran Gramatikal Bahasa Arab Oleh Linguistik Arab (Studi Tokoh Lintas Madzhab Nahwu) - Hakmi Wahyudi; Hakmi Hidayat; Sri Wahyuni Hakim (AL-FIKRA, 2020)
The grammatical thinking of Arabic begins with the phenomenon of giving a society and how to read words in Arabic both before Islam and after the spread of Islam. If the benchmarks are from Islam then the grammatical is related to the Qur'an but if with before Islam the grammatical Arabic is related to Arabic words such as poetry and Arabic prose. Grammatical development also grows and develops according to the early pioneers and learning methods. So that each grammatical cleric of Arabic composes independently until the grammatical is mature epitimologies, each grammatical cleric of Arabic is like a teacher and student relationship. The Aim this study is illustrate how each grammatical thinker of Arabic language originates and develops the grammatical, so that it becomes a standard science until now as linguistic studies in linguistics. This research is a qualitative research with descriptive method with data analysis in the form of data interpretation called ta'wil and hermeneutics. The findings of this research are self-composed science in the grammatical history of Arabic such as Uslub Taajjub, harakat and the point by Abu Aswad ad Duali, Arudh Qawafi by Khalil Ahmad Al Farahidi, taukid and ‘ataf Bayan by Sibawaiyh. Lafadz and Meaning by Ibn Jinni, al Ma’ani by Jurjani and other Arabic grammatical scholars.Pemikiran linguistik bahasa arab berawal dari fenomena untuk memberikan harakat dan cara membaca  sebuah kata-kata dalam bahasa arab baik sebelum Islam maupun setelah menyebarnya agama Islam. Jika tolak ukurnya dari Islam maka gramatikal tersebut berhubungan dengan al Qur’an tapi jika dengan sebelum Islam maka gramatikal bahasa arab tersebut berhubungan dengan kalam-kalam Arab.  Perkembangan gramatikal pun tumbuh dan berkembang sesuai perintis awal dan perkembangannya. Sehingga masing-masing ulama gramatikal bahasa arab menyusun secara mandiri walaupun sebelumnya disusun gramatikal tersebut, setiap ulama gramtikal bagaikan hubungan guru dan murid. Tujuan penelitian ini pun menggambarkan bagaimanakah masing pemikir gramatikal bahasa arab mencetus dan mengembangkan gramatikal tersebut, sehingga menjadi ilmu yang baku sampai sekarang sebagai kajian-kajian linguistik dalam ilmu bahasa . Penelitian ini bersifat kualitatif dengan metode deskriptif dengan analisis data berupa interpretasi data yang disebut dengan ta’wil dan hermeneutika.